Reproducibility of facial soft tissue landmarks on facial images captured on a 3D camera - Othman Siti Adibah; Ahmad Roshahida; Merican Amir Feisal; Jamaludin Marhazlinda (Sciendo, 2013)
Objective: Fast and non-invasive systems of the three-dimensional (3D) technology are a recent trend in orthodontics. The reproducibility of facial landmarks is important so that 3D facial measurements are accurate and may be applied clinically. The aim of this study is to evaluate the reproducibility of facial soft tissue landmarks using a non-invasive stereo-photogrammetry 3D camera.